PS17 Commissioning Care for People with Long Term Conditions. (17th September 2012) - Porter, AM; Smith, JA; Shaw, S; Mays, N
Abstract : Background: The landscape of health care commissioning is being reshaped in England, as clinical commissioning groups prepare to take on the role now held by Primary Care Trusts (PCTs). Long term conditions are likely to remain a priority area, with concerns about increasing prevalence driving a shift towards care delivered in the community and early intervention to avoid hospitalisation. We report on a NIHR-funded study which used action research in three NHS local health communities to examine in detail the practice of PCT commissioning of care for people with long term conditions. Methods: The study was undertaken in three contrasting PCT areas (Somerset, Wirral and Calderdale), and focused on diabetes and another locally selected condition in each site. The design combined a largely ethnographic approach with action research, allowing for responsive intervention to meet local commissioners' needs. Formal data collection over a 15 month period to January 2012 consisted of 104 semi structured interviews, observation of 27 meetings, and analysis of over 300 documents. A thematic framework was developed to guide analysis in terms of processes, resources and outcomes of commissioning. Results: Findings highlighted the complex nature of health care commissioning, far removed from the 'commissioning cycle' which sets out a formal, sequential model emphasising contracting. Instead, commissioning developments took place over a number of years through an incremental process of review and revision where negotiation and relationships were prominent. Providers often played a significant role in identifying needs and designing new models of care. The sheer scale of labour involved in commissioning was striking. Greatest success with shifting models of care towards nationally recommended good practice came where there was a combination of effective prioritisation of developments, persistence and pragmatic bounding of tasks within a wider strategic framework. Measuring the impact of commissioning practice on clinical outcomes was challenging. Conclusion: To fulfill national policy towards remodelling care for people with long term conditions, NHS commissioners are engaged in labour-intensive, steadily paced and incremental work with providers. Planned reforms to commissioning in England raise questions about whether this approach can continue in the face of straitened budgets for management support, an increased emphasis on provider competition and disruptions to established relationships between commissioners and providers.